2011
DOI: 10.1111/j.1525-142x.2011.00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor is crucial for development of the carapace in turtles

Abstract: Turtles are characterized by their shell, composed of a dorsal carapace and a ventral plastron. The carapace first appears as the turtle-specific carapacial ridge (CR) on the lateral aspect of the embryonic flank. Accompanying the acquisition of the shell, unlike in other amniotes, hypaxial muscles in turtle embryos appear as thin threads of fibrous tissue. To understand carapacial evolution from the perspective of muscle development, we compared the development of the muscle plate, the anlage of hypaxial musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 73 publications
2
42
0
Order By: Relevance
“…Hence, future experiments must evaluate whether MMN incubation decreases yolk and egg size and/or if it shifts their biochemical composition. It will be also useful to study expression and methylation patterns of genes that are involved in modulating fetal growth (e.g., hepatocyte growth factor; Kawashima-Ohya et al, 2011). In spite of these limitations, the differential effects (and the absence of them; e.g., carapace length) that MMN incubatory conditions had on various morphological parameters and on corticosterone serum levels still support the general inference of this work, namely, MNN promotes stress in turtle fetuses.…”
Section: Discussionmentioning
confidence: 62%
“…Hence, future experiments must evaluate whether MMN incubation decreases yolk and egg size and/or if it shifts their biochemical composition. It will be also useful to study expression and methylation patterns of genes that are involved in modulating fetal growth (e.g., hepatocyte growth factor; Kawashima-Ohya et al, 2011). In spite of these limitations, the differential effects (and the absence of them; e.g., carapace length) that MMN incubatory conditions had on various morphological parameters and on corticosterone serum levels still support the general inference of this work, namely, MNN promotes stress in turtle fetuses.…”
Section: Discussionmentioning
confidence: 62%
“…Accordingly, we found that b-catenin was specifically translocated into the nucleus of the CR ectodermal cells at stage TK14, when the CR is clearly visible (Kuraku et al, 2005); no equivalent expression patterns have been observed in non-turtle embryos. Although we had previously hypothesized that HGF/c-Met pathway might have had a role in the b-catenin translocation, Hgf is, while nearby, actually not expressed in the CR (Kawashima-Ohya et al, 2011, Nagashima et al, 2014. However, the distribution of the HGF protein and a putative role in the CR formation is unknown, and thus require further investigation.…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies of turtle development and paleontology (CebraThomas et al, 2005;Nagashima et al, 2007;Li et al, 2008;Moustakas, 2008;Sánchez-Villagra et al, 2009;Kawashima-Ohya et al, 2011;Kuratani et al, 2011;Hirasawa et al, 2013) have advanced our understanding of the evolutionary origin of turtles and the genetic and cellular interactions that regulate various aspects of bone development in the carapace. However, the genetic regulation of the origin and evolution of the epidermal scutes has not been addressed.…”
Section: Introductionmentioning
confidence: 99%